Preliminary study on the seasonal questing of Ixodes ricinus group ticks in Ain Draham forest (north-western Tunisia) with analyses of their phylogenetic diversity - Elati, Khawla; Khammasi Khbou, Médiha; Kahl, Olaf; Mwacharo, Joram; Al-Shamaa, Khaled; Rekik, Mourad; Darghouth, Mohamed Aziz; Gharbi, Mohamed (Elsevier, 2023)
The present study aimed to investigate the activity dynamics of Ixodes ricinus group ticks in a forest located in north-western Tunisia (Aïn Draham, Jendouba District) and assess the variation of abiotic factors (temperature, Normalized Difference Vegetation Index and relative humidity) during one year survey from September 2016 to August 2017 using the dragging sampling method. A total of 116 questing ticks was collected from the vegetation consisting of 47 adults (19 females and 28 males, sex ratio M:F = 1.47), 45 nymphs and 24 larvae representing 40.5, 38.8 and 20.7% of the total collected specimens, respectively. Adult I. ricinus were collected during October–May, nymphs during May–August and larvae during July–September. There were statistically significant correlations between adult tick numbers and mean daily relative humidity (Pearson r = 0.77; p = 0.003) and mean daily temperature (r = −0.74; p = 0.006).